Immunologic and clinical features of bacterial uveitis - E. A. Kleshcheva; S. A. Kochergin; G. Sh. Arzhimatova; A. E. Kleshchev; N. V. Mel'nikova; E. V. Shirshova (Российский офтальмологический журнал)
Bacterial infection is one of the etiologic factors of inflammation of the uvea. Bacterial agents capable of provoking the development of uveitis are numerous and diverse (Gram-positive and Gram-negative; bacilli, cocci, and flagellates; aerobic and anaerobic). It is important to note that bacterial infection can cause uveal inflammation through several pathogenetic pathways. Direct exposure to microorganisms and products of their vital activity is only one of the realized pathological influences. The pathogenetic mechanisms of uveal inflammation development are not completely clear, but the leading role is currently attributed to activation of Toll-like and Nod-like receptors by bacterial antigens with subsequent triggering of a cascade of reactions leading to the production of inflammatory cytokines. In addition, a significant role is given to autoimmune processes, as a result of which cross-reactivity to bacterial antigens and similar antigens of the ocular vasculature develops. The peculiarities of pathogenesis provide the peculiarities of the clinical picture of bacterial uveitis, which is characterized by granulomatous type of inflammation. The exception is uveitis developing due to the predominance of autoimmune component in the development of the disease, which determines pathomorphological nongranulomatous type of inflammation. In this review immunologic mechanisms of bacterial uveitis development are given, pathogenesis of syphilitic, tuberculous, post-streptococcal uveitis is considered in more detail. Pathomorphologic and clinical features of bacterial uveitis are described. The role of modern drugs in the treatment of bacterial inflammation of the ocular vasculature is evaluated.